Asuhan Kebidanan Pada Ibu Bersalin Primigravida Dengan Partus Lama Di Klinik Pratama Siti Kholijah JL. Marelan I, Terjun, Kec. Medan Marelan - Rahmawani Fauza (Journal of Health and Medical Science, 2024)
Prolonged labor is labor that lasts more than 24 hours in primi, and more than 18 hours in multi.(Murnika, 2015) Globally, about 8-11% of pregnant women experience abnormalities in the 1st stage of labor. Delayed labor in the active phase was found in 25% of nulliparous women and 15% of multiparous women. A study in Sweden found that 23% of patients about to go into labor experienced a delay in progress in the latent phase. The study also found that the delay in progress was more common in nulliparous women than multiparous women (29.2% vs. 17). Long parturition is one of the contributors to maternal mortality in the world, based on WHO in 2014 there were cases of prolonged labor in women in the world, namely 289 per 100,000 live births. Meanwhile, in Indonesia, the incidence of prolonged labor is the highest in ASEAN, namely 359 per 100,000 live births, mothers die from prolonged labor (WHO, 2014). Researchers provide comprehensive midwifery care for pregnant women, maternity, postpartum, BBL, neonates and family planning using a midwifery management approach to Mrs "I" with a case of prolonged labor. Methods care in this study by observation and evaluation. The subject of this care is Mrs "I" with a long labor at the Siti Kholijah Primary Clinic. Comprehensive midwifery care for Mrs. "I" during the third trimester of pregnancy, in labor with prolonged labor and spontaneous delivery, during the postpartum period with normal childbirth, BBL with BBLN, neonates with normal neonates, and being an acceptor for condom. This research activity is about handling long parturition in maternity mothers. Researchers conducted observations and evaluations to mothers on a regular basis. Observations and evaluations were carried out not only knowing and assessing contractions and progress of labor but also knowing and assessing emotional conditions, levels of fatigue, and support for mothers. The mother's hydration status also needs to be considered and if possible, the mother can be asked to eat small portions so that she can gather energy for delivery. This research was conducted at the Pratama Siti Kholijah clinic, on April 18, 2022. This observation and evaluation began at 21.30 WIB until the mother carried out a normal delivery process until the fourth stage on April 20, 2022 at 22.30.